Raman spectroscopy methods for investigating supported lipid bilayers - Sweetenham, Claire Sue (2011)
This work is centred on the development of Raman spectroscopy methods for investigating supported lipid bilayers (SLBs). These nanoscale, biological structures have found wide application as models of cellular membranes in many areas of scientific research. They consist of phospholipid molecules that self-organise into bilayer structures containing phase-separated microdomains, which play an important role in many biological processes. SLBs are well-defined and stable under a variety of conditions, allowing characterisation with a broad range of physical methods. However, many of these techniques provide purely a visualisation of the surface or disturb the bilayer with labelling. Raman spectroscopy can offer a non-invasive chemical and structural analysis of SLBs and microdomains. A Raman microspectroscopy (RMS) system with integrated atomic force microscope (AFM) has been developed and characterised for studying SLBs. This experimental setup combines the benefits of Raman spectroscopy with the high spatial resolution of confocal microscopy. Furthermore, the incorporation of AFM makes it possible to directly correlate chemical information and spatial features. Experiments are carried out to determine the capabilities of this system for investigating SLBs. A variety of substrates are considered for this application and only prolonged expose to high laser powers is found to have any effect on the Raman spectrum of lipids. However, a single SLB cannot be detected with RMS, so focus turns to employing scatteringenhancing techniques. Surface-enhanced Raman spectroscopy (SERS) substrates formed by nanosphere lithography (NSL) are developed to be used with the combined AFM-Raman system. Simultaneous topographical imaging and highsensitivity chemical mapping of molecular monolayers deposited across these substrates reveals the distribution and magnitude of electric field enhancement that they can provide. These measurements are supported by calculations and finite element method (FEM) simulations. Then similar experiments are performed on substrates covered with a bilayer of fatty acid molecules. Considering the close similarities between these molecules and phospholipids, this demonstrates the potential of combined AFM and SERS with NSL substrates for detecting SLBs and imaging the phase-separated microdomains they form. Finally, functionalised AFM probes are developed for tip-enhanced Raman spectroscopy (TERS) using dielectrophoresis (DEP). This phenomenon is generated within a conductive AFM setup to guide nanoparticles towards an AFM probe to cluster and grow at its tip apex. This growth is monitored with force spectroscopy and a variety of imaging parameters. The probes are then analysed with scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDX) to confirm the accumulation of nanoparticles on the tip both physically and chemically. The TERS activity of these functionalised probes is investigated with the combined AFM-Raman system, which demonstrates an enhancement of scattering when the tip apex of the probe and the laser are aligned.